Pengaruh Pelatihan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Bagian PT. PCI Elektronik International - Nur Rahmah Andayani; Priskila Makian (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
This study aims to determine the effect of job training and work motivation on employee performance in the Production department employees of PT. PCI Electronics International. Respondents are employees of the production department PT.PCI Electronics International. This study uses multiple regression analysis, where are these tools used to determine the extent of the effect of job training and work motivation on employee performance. The results of this study indicate that the variable partial job training and motivation has a positive and significant impact on employee performance. And simultaneous research shows that all independent variables have positive and significant influence on employee performance.